2021
DOI: 10.3233/jad-201481
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Homocysteine and Vitamin Levels in Demented Patients

Abstract: Background: Although it is known that the nutritional status among elderly persons and, in particular, patients with dementia, is compromised, malnutrition that results in insufficient uptake of several vitamins is often not diagnosed. Objective: An elevated homocysteine level is a known strong risk factor for vascular dementia (VaD) and Alzheimer’s disease (AD). Several B vitamins are involved in the metabolism of homocysteine. Therefore, we investigated the serum levels of vitamin B1, vitamin B6, folate, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 79 publications
0
14
0
Order By: Relevance
“…Results of the previous studies (Luchsinger et al, 2004;Ma et al, 2017) were inconsistent, but the overall results showed that elevated tHcy levels were associated with an increased risk of cognitive impairment, vascular dementia, and AD (Clarke et al, 1991;Seshadri et al, 2002;Ravaglia et al, 2005). The folate and vitamin B12 deficiency might impair methylation reactions to be involved in the pathogenesis of AD (Selhub et al, 1993;Hoffmann et al, 2021). In addition, folate and vitamin B12 are important mediators of tHcy levels, indirectly correlated with AD (Selhub et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Results of the previous studies (Luchsinger et al, 2004;Ma et al, 2017) were inconsistent, but the overall results showed that elevated tHcy levels were associated with an increased risk of cognitive impairment, vascular dementia, and AD (Clarke et al, 1991;Seshadri et al, 2002;Ravaglia et al, 2005). The folate and vitamin B12 deficiency might impair methylation reactions to be involved in the pathogenesis of AD (Selhub et al, 1993;Hoffmann et al, 2021). In addition, folate and vitamin B12 are important mediators of tHcy levels, indirectly correlated with AD (Selhub et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, folate and vitamin B12 are important mediators of tHcy levels, indirectly correlated with AD (Selhub et al, 1993). Accordingly, some (Clarke et al, 1998;Ravaglia et al, 2005;Hoffmann et al, 2021), but not all studies (Ma et al, 2017;Rabensteiner et al, 2020) have shown that low levels of folate and vitamin B12 were associated with AD. More recent studies have specifically addressed the association between a significant elevation of tHcy levels and neurodegenerative diseases including Parkinson's disease (PD) and multiple system atrophy (MSA; Zhang et al, 2015;Sleeman et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study [ 116 ], the HCy levels were measured in nine FTD and nine LBD, and no significant different was found, in either group, with respect to healthy controls.…”
Section: Homocysteine and Degenerative Brain Diseasesmentioning
confidence: 96%
“…Alternatively which is essential for of S-adenosyl-methionine (SAM) synthesis, and required for methylation of DNA/RNA and proteins ( 15 ), its impairment caused hypermethylated redox-related genes (NUDT15 and TXNRD1). Independently, B vitamins deficiency also induced cerebrovascular dysfunction, activation of tau kinases and enhanced Aβ metabolism contributed to AD development ( 16 18 ). David Smith and colleagues' studies also indicated a possible pathogenetic role of B vitamins (B12, Folate) in mild cognitive impairment, as B vitamins therapy could abrogate effects of iron-associated brain atrophy rate ( 19 ).…”
Section: Introductionmentioning
confidence: 99%